The Long-Awaited Rise of the Middle Class in Latin America Is Finally Happening - Maurizio Bussolo; Maryla Maliszewska; Elie Murard (Institute of Labor Economics (IZA), 2017)
In many developing countries, the supply of skilled workers is likely to continue to be stronger than demand, and this should drive down the skill premium and reduce inequality. Within the limitations of any exercise based on simulations, this paper finds that the recently observed reduction in inequality in Latin America may continue. Building on counterfactual scenarios projecting economic and demographic (including age and education) growth, the paper also highlights that by 2030 the long-awaited rise of the middle class in Latin America will be in full swing, as its share will be 43 percent of the region's population, twice the value in 2005. This achievement is not guaranteed, as countries with large initial inequalities will have to achieve very high rates of inclusive growth.
Keywords: D31; D58; I24; J11; 330; Latin America; skill premium; middle class; inequality